2021
DOI: 10.3390/jcm10091865
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Row Carpectomy with Total Scapoidectomy vs. Conventional Carpal Resection for ReMotion Total Wrist Arthroplasty

Abstract: High complication rates in total wrist arthroplasty (TWA) still lead to controversy in the medical literature, and novel methods for complication reduction are warranted. In the present retrospective cohort study, we compare the outcomes of the proximal row carpectomy (PRC) method including total scaphoidectomy (n = 22) to the manufacturer’s conventional carpal resection (CCR) technique, which retains the distal pole of the scaphoid (n = 25), for ReMotion prosthesis implantation in non-rheumatoid patients. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…In this regard, we advocated for the PRC implantation technique, especially in SLAC and SNAC wrists. Thereby, radial impaction syndrome can be significantly reduced [ 13 ] and issues related to the sclerotic deformed scaphoid can be prevented due to its total removal. Recent advances in TWA’s implant design and materials have massively improved the initially high complication rates [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we advocated for the PRC implantation technique, especially in SLAC and SNAC wrists. Thereby, radial impaction syndrome can be significantly reduced [ 13 ] and issues related to the sclerotic deformed scaphoid can be prevented due to its total removal. Recent advances in TWA’s implant design and materials have massively improved the initially high complication rates [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients received TWA using the ReMotion Total Wrist System (Stryker, Kalamazoo, Michigan). Several cases were already included in our previous study reporting non-rheumatoid patients [ 6 ] as well as the study comparing the PRC technique to the conventional carpal resection method [ 13 ]. One level IV surgeon performed the former ( Figure 1 b) and two other level IV surgeons performed the latter technique [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the proximal row was completely removed to prevent the patient from reoperations due to carpal OA. Although we could prove in a previous study that PRC is a reliable surgical technique for total wrist arthroplasty [14], we decided against implanting the carpal component of the ReMotion prosthesis due to the patient's manifest osteoporosis. According to the World Health Organization, osteoporosis is defined as a metabolic bone disease characterized by low bone mass and microarchitectural deterioration of bone tissue causing progredient bone fragility and a higher risk for fracture [21].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we decided to perform a WHA as secondary surgery, which was finally performed 3 months after the initial trauma or first surgery, respectively. Our technique included a common dorsal approach and a PRC was performed as the first step [14]. Afterwards, the distal carpal row presented with an intact cartilage layer, while the joint surface of the distal radius was completely destroyed and palmarly dislocated.…”
Section: Case Presentationmentioning
confidence: 99%
“…This represented a significant improvement over previous generation. In this context, studies have reported better results with the fourth generation of artificial wrist joints (Bidwai et al, 2013;Froschauer et al, 2021). In contrast to wrist fusion, TWA preserves wrist mobility and provides effective pain relief (Fischer et al, 2020;Berber et al, 2020;Matsui et al, 2020;Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%